2000
DOI: 10.1007/pl00000700
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear inositides: inconsistent consistencies

Abstract: It is now clear that phosphoinositides, which play a major role in the regulation of a variety of cellular processes in the cytoplasm, are found within the nucleus. Their role in this subcellular compartment is still contentious: however, data has suggested that nuclear inositides generate substrates, such as PtdIns(4,5)P2, utilised by a number of nuclear signalling pathways: for example, nuclear phospholipase C and the PtdIns 3-kinase cascade. There is also evidence that PtdIns(4,5)P2 may play a role in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 166 publications
(208 reference statements)
1
29
0
Order By: Relevance
“…The presence of inositide-modifying enzymes and independent lipid pools within the nucleus also supports the hypothesis that inositide pathways function within the nucleus (37,38). Pik1, an essential phosphatidylinositol 4-kinase, and Mss4, an essential phosphatidylinositol-4-phosphate (PI(4)P) 5-kinase, are both required for PI(4,5)P 2 production in budding yeast (39,40).…”
supporting
confidence: 64%
“…The presence of inositide-modifying enzymes and independent lipid pools within the nucleus also supports the hypothesis that inositide pathways function within the nucleus (37,38). Pik1, an essential phosphatidylinositol 4-kinase, and Mss4, an essential phosphatidylinositol-4-phosphate (PI(4)P) 5-kinase, are both required for PI(4,5)P 2 production in budding yeast (39,40).…”
supporting
confidence: 64%
“…4C). Given the many studies documenting the occurrence and directionality of the IP 3 and ryanodine receptors on the inner nuclear membrane (8,48) as well as the existence of a nuclear phosphoinositol cycle (13,12), mGlu5 receptors oriented in the latter fashion would be ideally situated to activate nuclear PLC/IP 3 /Ca 2ϩ cascades. The question arises then as to what ligand activates these receptors and how does it do so.…”
Section: Discussionmentioning
confidence: 99%
“…Many components of G protein signaling pathways are also found in the nucleus or associated with nuclear membranes. These include phospholipase C isozymes (11,12), nuclear inositol phosphates (12,13), DAG (13), PKC isozymes (14), adenylate cyclase (15), regulators of G protein signaling (RGS proteins; Refs. 16 and 17) as well as heterotrimeric G proteins themselves (18).…”
Section: Changes In Nuclear Camentioning
confidence: 99%
“…The presence in the nucleus of both polyphoshoinositides and the enzymes responsible for their metabolism has suggested that they may constitute a signaling system [Divecha et al, 2000;Irvine, 2003]. It is noteworthy that nuclear inositol lipid metabolism is independently regulated from its plasma membrane counterpart and is modulated in response to short-term growth factor signaling, cell cycle progression and during differentiation [Martelli et al, 2004].…”
mentioning
confidence: 99%